Mapping the travel blog : a study of the online travel narrative - Azariah, Deepti Ruth (Curtin University, 2012)
This thesis examines the discursive tension between travel and tourism and analyses how narrative techniques negotiate this in travel blogs. This discursive analysis uses various theories of narrative and self-presentation, particularly Bakhtin’s heteroglossia, polyphony, and speech genres, Goffman’s theories of self-presentation, and Graham Dann’s framework for tourist discourse. It finds that the underlying discursive tensions in travel blogs indicate a need for a more flexible approach to defining and analysing this form of communication.